2022
DOI: 10.1007/s10803-022-05674-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective Mutism in Children With and Without an Autism Spectrum Disorder: The Role of Sensory Avoidance in Mediating Symptoms of Social Anxiety

Abstract: Selective mutism in children with and without an autism spectrum disorder: The role of sensory avoidance in mediating symptoms of social anxietyDespite Selective Mutism (SM) and Autism Spectrum Disorder (ASD) often presenting together in clinical practice, there is no research to guide assessment processes (McKenna et al., 2017), with earlier editions of the DSM hindering professionals' readiness to diagnose ASD and SM together (Valaparla et al., 2018). While SM is currently characterised as an anxiety disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In line with this conclusion, there are indications that SM is associated with autism spectrum disorder (ASD). Although it should be noted that relatively few studies have explored this issue, probably as a result of the rather ambivalent exclusion criterion as adopted in the DSM, it has been found that clinically referred children with SM often have a comorbid diagnosis of ASD [22,23] and display elevated scores on measures of autistic traits [24,25]. Admittedly, there is also research showing that children with SM do not exhibit heightened scores on a quantitative scale of autistic traits [26], but it is important to note that this study excluded children with SM who were high on the autism spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this conclusion, there are indications that SM is associated with autism spectrum disorder (ASD). Although it should be noted that relatively few studies have explored this issue, probably as a result of the rather ambivalent exclusion criterion as adopted in the DSM, it has been found that clinically referred children with SM often have a comorbid diagnosis of ASD [22,23] and display elevated scores on measures of autistic traits [24,25]. Admittedly, there is also research showing that children with SM do not exhibit heightened scores on a quantitative scale of autistic traits [26], but it is important to note that this study excluded children with SM who were high on the autism spectrum.…”
Section: Introductionmentioning
confidence: 99%